The Role of the Artist in a Communal Art Project - Kuizinaitė, Aurelija; Jurėnienė, Virginija (Vilnius University Open Series, 2022)
Art Project Management is a limited time process and a specific way of thinking that ensures that all the project stages are carried out in a planned and structured manner, that the project is finished with successful implementation of the aim of the project (MPSI, 2016, p. 71). When analysing art projects, Dovydaitytė emphasises they are often characteristic of a process, interdisciplinarity and multi-directional relations with a wider social context (Dovydaitytė, 2014). When carrying out a communal art project in a community, an artist can perform the following different functions: facilitator, interpreter, trainer, animator, mentor, consultant, project manager. Scientists attribute functions to artists differently in communal art projects. Often, communal art projects include a professional artist who comes with one of the roles that s/he has, curates the entire process and is responsible for management and, of course, engages the community. Moreover, an artist can be not only the creator, but also the manager of the whole project. The main role of a project manager is to unite members of the community, help them collaborate, and ensure as well as evaluate the final results of the art project.
Keywords: communal art project; role of the artist; management; art project; project management; community; community art project